2006
DOI: 10.1542/peds.2005-0142
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Testing and Clinical and Demographic Profile of Adolescents With Non–Perinatally Acquired HIV Infection

Abstract: OBJECTIVES. We sought to examine the demographic, clinical, and behavioral characteristics; reasons for HIV testing; and factors that contribute to delays in entry into specialized HIV care after diagnosis of HIV infection among adolescents in an urban clinic in Georgia.METHODS. All of the data for this study were obtained solely by medical chart review. Demographic, clinical, behavioral, and HIV testing data were abstracted from medical charts of 59 non-perinatally HIV-infected adolescents who were aged 13 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…There is evidence that at least 20% of newly diagnosed youth seroconverted within the previous 6 months. 37 This early phase of illness is a time of high viremia, during which the risk of infectivity and transmission is greatest. People who are aware of their HIV status are more likely to practice safer sex or remain abstinent.…”
Section: Implementation Of Hiv Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that at least 20% of newly diagnosed youth seroconverted within the previous 6 months. 37 This early phase of illness is a time of high viremia, during which the risk of infectivity and transmission is greatest. People who are aware of their HIV status are more likely to practice safer sex or remain abstinent.…”
Section: Implementation Of Hiv Screeningmentioning
confidence: 99%
“…Adolescents are more likely to agree to be tested if it is recommended by a physician, 40 and youth who are diagnosed at a health care facility are more likely to enter into HIV care in a timely fashion. 37 The 2007 National Health Interview Survey found that among adults who received an HIV test, more than 80% did so in doctors' offices, hospitals, emergency departments, and clinics compared with test- …”
Section: Implementation Of Hiv Screeningmentioning
confidence: 99%
“…The most common reasons youth, including Aboriginal youth, seek an HIV test are because they have been advised by a health care worker; have engaged in a high risk behavior (i.e., injection drug use, unprotected sex); for prenatal screening; or because they are feeling sick (Bucharski et al, 2006;Grant et al, 2006;Mackellar et al, 2006;RotheramBorus, Gillis, Reid, Fernandez, & Gwadz, 1997;Samet & Winter, 1997). Very little information is available about youth perceptions on test counseling; however, one study of HIV testing sites in the USA reported that only 28% of youth said the counselor did a ''good'' job helping them identify their HIV risk behaviors (Schneir, Belzer, & Adivi, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Although approximately half of the newly diagnosed teens with behaviorally acquired HIV infection still have preserved immune function and do not require immediate combination antiretroviral therapy (cART) initiation [32], most perinatally infected teens are already on long-term antiretroviral therapy, often with a history of treatment changes in the past. For the Pediatric Spectrum of HIV Disease Study cohort of 2000 HIV-infected children and adolescents in the United States, the proportion of patients receiving three or more sequential triple-therapy regimens increased from 4% to 17% during 1997 to 2001, whereas the durability of cART decreased from 13 to only 7 months from the fi rst to third cART regimen [33••].…”
Section: Provision Of Clinical Carementioning
confidence: 99%